Cytotoxic Activity of Citral from Cymbopogon nardus as Anticancer of MCM-B2 Cell - Hasim Hasim; Surya Pangidoan Nasution; Silvi Octavia Kurniawati; Indah Rachmawati (Current Biochemistry, 2020)
Cancer is a deadly disease caused by cell abnormalities characterized by uncontrolled cell growth. One type of cancer that is the second leading cause of death is breast cancer. Lemongrass (Cymbopogon nardus) is a plant containing citral and geraniol which has the potential as an anticancer. This research was aimed to analyze the potential of essential oils from citronella as antiproliferation of MCM-B2 breast cancer cells. The results of this research showed that lemongrass essential oil was able to significantly reduce the growth of MCM-B2 cancer cells (p<0.05). The concentration of 3 ppm showed an significant difference in doxorubicin, and the concentration of 24 ppm had the highest inhibitory activity with an IC50 value of 5.38 ppm. Keywords: Antiproliferation, breast cancer, MCM-B2, essential oils, fragrant lemongrass